2013
DOI: 10.1186/1939-4551-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Allergic conjunctivitis and the most common allergens in Northern Greece

Abstract: BackgroundOcular allergies affect a great part of the general population and often co exist with other allergic manifestations. In the present study, the prevalence of allergic conjunctivitis and the commonest allergens in allergic patients at an outpatient unit in Thessaloniki, Greece were evaluated.MethodsThis is a retrospective study regarding allergic patients who referred to an outpatient clinic between the 1st of January of 1996 and the 31st of December 2010. They completed relative questionnaires concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…These results indicate that the main risk factor for experience of OS is sensitisation to outdoor aeroallergens. Our results are similar to the results of recent studies (9,38).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that the main risk factor for experience of OS is sensitisation to outdoor aeroallergens. Our results are similar to the results of recent studies (9,38).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, cat dander is a component of house dust allergens, even in homes where a cat has never lived 24,25,34 . Most of the studies have found cat dander as a major source of allergen as in our study (11%) 35 .…”
Section: Discussionsupporting
confidence: 50%
“…In the study conducted by Almaliotis et al (12), AC was detected in 40.11% of 1239 AR patients. Patients with ophthalmic allergy symptoms were diagnosed with conjunctivitis by an ophthalmologist in this study.…”
Section: Discussionmentioning
confidence: 89%